Investigating the influence of chatbots on customer experience and frustrations in self-help functions in South Africa - Raphela, Lesego Jerminah Mmakgopa (University of the Witwatersrand, Johannesburg, 2023)
Organisations must provide responsive, efficient, and 24/7 customer service in the ever-evolving digital era. Chatbots have emerged as the preferred Artificial Intelligence (AI) technology, offering self-help functions to users in need of various digital services. This study addressed the scarcity of empirical studies on the use of chatbots as self-service agents in South African companies, particularly in exploring their contribution to customer experiences, both positive and negative. The study extended the Technology Acceptance Model (TAM) to investigate the antecedents of customer chatbot engagement and their subsequent impact on customer satisfaction and frustration within the context of self-help functions. Utilising a quantitative approach, data was collected through online survey questionnaires from a sample of 258 participants who had interacted with chatbots. Multiple linear regression analysis was employed for data analysis. Results revealed that perceived ease of use, performance expectancy, compatibility, and social influence positively influenced customer chatbot engagement. Additionally, customer engagement with chatbots had a significant positive correlation with satisfaction and a negative correlation with frustration. These results suggested that enhancing user-friendly interfaces, ensuring optimal performance, aligning with user preferences, and leveraging social influence could foster increased engagement. This study stressed the significance of understanding and optimising customer chatbot engagement for a positive user experience.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Chatbot engagement; Customer experience; Self-help tools; Artificial intelligence; Customer service; Customer satisfaction; Customer frustrations; UCTD; SDG-8: Decent work and economic growth